Human endometrial stromal cell decidualization requires transcriptional reprogramming by PLZF†. Issue 1 (25th November 2017) - Szwarc, Maria M; Hai, Lan; Gibbons, William E; Peavey, Mary C; White, Lisa D; Mo, Qianxing; Lonard, David M; Kommagani, Ramakrishna; Lanz, Rainer B; DeMayo, Francesco J; Lydon, John P
Abstract: Infertility and early embryo miscarriage is linked to inadequate endometrial decidualization. Although transcriptional reprogramming is known to drive decidualization in response to progesterone, the key signaling effectors that directly mediate this hormone response are not fully known. This knowledge gap is clinically significant because identifying the early signals that directly mediate progesterone-driven decidualization will address some of the current limitations in diagnosing and therapeutically treating patients at most risk for early pregnancy loss. We recently revealed that the promyelocytic leukemia zinc finger (PLZF) is a direct target of the progesterone receptor and is essential for decidualization of human endometrial stromal cells (hESCs). The purpose of this current work was to identify the genome-wide transcriptional program that is controlled by PLZF during hESC decidualization using an established in vitro hESC culture model, siRNA-mediated knockdown methods, and RNA-sequencing technology followed by bioinformatic analysis and validation. We discovered that PLZF is critical in the regulation of genes that are involved in cellular processes that are essential for the archetypal morphological and functional changes that occur when hESCs transform into epithelioid decidual cells such as proliferation and cell motility. We predict that the transcriptome datasets identified in this study will not only contribute to a broader understanding of PLZF-dependent endometrial decidualization at the molecular level but may advance the development of more effective molecular diagnostics and therapeutics for the clinical management of female infertility and subfertility that is based on a dysfunctional endometrium. Summary Sentence: PLZF drives progesterone-dependent transcriptional reprogramming of the human endometrial stromal cells to enable decidualization.